Implementation of Character Education in the Society 5.0 Era on Accounting Education Students, Universitas Muhammadiyah Surakarta - Harsono, H; Thoyibbah, Kartika; Narimo, Sabar (Universitas Muhammadiyah Surakarta, 2022)
The era of Society 5.0 is an era where humans are required to innovate, be creative, and be able to understand science and technology. Strengthening character education needs to be applied to form good morals based on national character in era of Society 5.0. The purpose of this study was to determine the implementation of character education in the Accounting Education Study Program, University of Muhammadiyah Surakarta. In addition, this study aims to determine the challenges in implementing character education in the era of Society 5.0. This type of research is qualitative research with a site data analysis research methods. The results of the study indicate that character education is important which is carried out by utilizing technology and information. Implementation carried out in the form of religious values, nationalism, integrity, independence, and mutual cooperation.